PEMBERDAYAAN WARGA DESA LARANGAN KULON WONOSOBO DALAM BUDIDAYA STROBERI SECARA HIDROPONIK - R Susanti (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
The Covid-19 pandemic that has occurred since the end of 2019 until now, requires people to reduce activities outside the home, and increase activities at home. This makes people's productivity levels decrease. One of the efforts to reduce the activity of residents gathering and doing activities outside the home is to provide alternative activities at home. This community service activity is intended to provide education and skills for hydroponic strawberry cultivation as an alternative activity at home that is healthy for humans and the environment around the residents of Larangan Kulon Village, Mojotengah District, Wonosobo Regency, Central Java. To achieve this goal, several method steps were used, namely observation, lectures/counseling,  demonstrations, and direct practice of the application of hydroponic strawberry plants. The service activity succeeded in transferring the knowledge and skills of hydroponic strawberry cultivation to the participants. Participants' understanding of concepts, tools and materials, cultivation and care methods and types of hydroponics is very good, as evidenced by 78.13% of participants getting a score of ≥80. Hydroponic cultivation of strawberry plants can be practiced by participants and can be used as an alternative to productive activities at home